ANTITUMOR INHIBITION OF NATURAL DRUGS IN COMBINATION WITH CYTOSTATICS FOR DRUG-RESISTANT TUMORS - K. D. Rakhimov (Scientific Journal of Pedagogy and Economics, 2019)
Drug-resistant Pliss lymphosarcoma strains are resistant to both herbal and cytostatics, and sarcoma 45 is resistant only to synthetic drugs. Manifestation of cross, multiple resistance to both natural and well-known anticancer drugs in resistant strains of Pliss lymphosarcoma, sarcoma 45, lymphocytic leukemia L 1210 has place. Collateral sensitivity to known chemotherapy drugs was revealed in drug-resistant variants of Pliss lymphosarcoma and in new natural preparations in resistant strains of sarcoma 45, L 1210. Induced drug resistance of Pliss lymphosarcoma, sarcoma 45 and L 1210 is removed by new herbal compounds or their combinations with antitumor drugs, changing the dose and number of combinants. The results of experimental studies for overcoming the emerged drug resistance with natural drugs in 1/2 MTD in a few (2 and 4) hours before the start of treatment with nitrosomethylurea, platidiam and adriamycin serve as a criterion for predicting clinical efficacy in patients with drug resistance to these drugs.